Killing Custer - Coel, Margaret, 1937- (Coel, Margaret, 1937- Wind River mystery., 2013)
When Colin Morningside, a descendant of Crazy Horse, is accused of murdering a General Armstrong Custer impersonator, Father John O'Malley and Vicky Holden must find the truth, which leads them into a deadly conspiracy that neither of them could have foreseen.